Optimalisasi Sumber Daya Manusia di Lembaga Amil Zakat Pengurus Wilayah NU Care-LAZISNU Daerah Istimewa Yogyakarta dalam Mewujudkan Kesejahteraan Masyarakat: Optimizing Human Resources at the Amil Zakat Management Institution for the NU Care-LAZISNU Special region of Yogyakarta in Realizing Social Work Goals - Mella Putri Ayuningtyas; Yuniyasari; Lessy, Zulkipli (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
This research aims to analyze several problem formulations, including: 1) examining the optimization of amil zakat in PWNU Care, 2) the impact of amil zakat optimization on program success at LAZISNU Care, 3) the impact of amil zakat optimization on the realization of the welfare state. This research uses descriptive qualitative research. The data collection method used is through observation, documentation and interviews with the director, secretary of the board of directors, manager of the Public Relations division, and manager of the fundraising division at PW NU CARE-LAZISNU DIY. The results showed that the management of amil zakat in PW NU CARE LAZISNU DIY is carried out by applying the functions that exist in human resource management, in the form of planning, organizing, directing, controlling, procurement, development, compensation, integration, maintenance, discipline, dismissal. Good management of amil zakat will produce optimal programs such as programs in LAZISNU DIY, namely, a) economic programs in the form of cash and non-cash assistance, b) education programs in the form of educational scholarships, c) health programs in the form of health assistance and free ambulance facilities, d) humanitarian programs in the form of assistance to natural disasters. The creation of programs that can help the welfare of the community, competent amil zakat in LAZISNU DIY is considered capable of helping social workers in realizing their ideals, namely the creation of a welfare state.